A time-delay technique to improve GBW on negative feedback amplifiers - Alves, L. N.
This paper presents a new method to improve the GBW (gain-bandwidth product) on negative feedback amplifiers. The proposed method is based on the introduction of time-delay elements in the feedback loop, which can be exploited to retrieve significant bandwidth enhancements. This delayed feedback concept is analyzed, and considerations are presented for first-order amplifiers, based on theoretical analysis. The concept is simulated and further demonstrated in a practical example using a series-shunt feedback amplifier with a TL081 operational amplifier (OA) and a 36-m-long coaxial cable as a delay element. Measured experimental results show a maximum bandwidth improvement of almost 90%, from a theoretical maximum of 141%. Copyright © 2007 John Wiley & Sons, Ltd.